Analisls Perbandingan Kinerja Keuangan Pada PT Kalbe Farma Tbk dan Kimia Farma Tbk Periode 2014 - 2016 - Dini Rusqiati; Alyssa Tarayadipa (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
Abstract, The purpose of this research is to know the development of financial performance of PT Kalbe Farma Tbk and PT Kimia Farma Tbk and to compare their financial performance analysis of both companies. This research is quantitative descriptive. The data used form of financial statements of PT Kalbe Farma Tbk and PT Kimia Farma Tbk period 2014-2016. Data analysis using financial ratio analysis, consisting of liquidity ratios, solvency ratios, profitability ratios, and activity ratios. The results showed, Liquidity Ratio of the Current Ratio of PT Kalbe Farma Tbk and PT Kimia Farma Tbk had good financial performance, the Cash Ratio and Quick Ratio PT Kalbe Farma Tbk had good financial performance and PT Kimia Farma Tbk had poor financial performance. Solvency Ratio from Debt To Equity Ratio and Long Term Debt To Equity Ratio PT Kalbe Farma Tbk and PT Kimia Farma Tbk have good financial performance. Total Debt To Total Assets Ratio PT Kalbe Farma Tbk has good financial performance and PT Kimia Farma Tbk has poor financial performance. Profitability Ratios of Gross Profit Margin at PT Kalbe Farma Tbk and PT Kimia Farma Tbk have good financial performance. Net Profit Margin, Return On Total Assets, and Return On Investment PT Kalbe Farma Tbk and PT Kimia Farma Tbk have poor financial performance. Activity Ratios for Receivable Turnover, Inventory Turnover, and Total Assets Turnover PT Kalbe Farma Tbk and PT Kimia Farma Tbk have poor financial performance. Fixed Assets Turnover PT Kalbe Farma Tbk has a poor financial performance and PT Kimia Farma Tbk has a good financial performance.